Response Surface Optimization for Extraction of Flavonoids from Artemisia lactiflora Wall. ex DC. and Evaluation of Antioxidant Capacities in vitro - Xiao, Meitian; Ye, Jing; Huang, Yayan; Zhang, Xueqin (Asian Journal of Chemistry, 2014)
Response surface methodology was used to optimize ultrasonic-assisted extraction of total flavonoids from Artemisia lactiflora Wall. ex DC. with a Box-Behnken design. The results indicated that the experimental yield of 6.396 ± 0.013 % was in good agreement with the value predicted by the model at the optimum extraction condition of ethanol concentration 53.5 % (v/v), liquid-to-solid ratio 22.95:1 (mL/g) and extraction time 23.2 min. The antioxidant activities of the purified extract were evaluated in vitro by 2,2-diphenyl-1-picrylhydrazyl, 2,2'-azino-bis(3-ethyl benzothiazoline-6-sulphonic acid) diammonium salt, ferric reducing antioxidant power and ferrous ion-chelating ability assays. In addition, nine flavonoids were isolated from A. lactiflora. for the first time. Among them, quercetin (compound 5) had the highest 2,2-diphenyl-1-picrylhydrazyl radical-scavenging activity with an IC50 of 7.6 ± 0.3 μM, indicating an important role of 5 for the antioxidant activity of A. lactiflora. The results showed that the flavonoids in this plant can be used as a source of potential antioxidants.